How Ghãtu Folk Dance Performance Promotes Tourism Industry in Nepal - Gurung, Raj Kumar (Tribhuvan University Journal, 2023)
This paper analyzes how Ghā̃tu promotes the tourism industry in Nepal. For conservation, the Nepal government does not seem to have promoted such cultural activities of the indigenous people that they are on the verge of extinction. Ghā̃tu, the nation’s cultural heritage, has several miraculous performances based on spiritual practices that attract tourists. The study attempts to make this Ghā̃tu folk dance performance one of the best sources of entertainment for tourists and domestic visitors to enhance the nation’s economy. The shaman tradition followed by this cultural activity, as the severing of the dancing girls, is another exciting activity that attracts the audience. So, every tourist should visit Nepal mostly to see such a performance once. The study’s findings show that many Ghãtu villages have not been considered tourist spots. And Nepal is not a popular tourist destination like France and Germany. Therefore, this paper proposes to make the Ghā̃tu village’s one of the most unavoidable tourist spots, which help sprout the tourism industry and help enhance the sustainable development of the nation. I have employed performance and semiotic theories developed by Schechner and Chandler and ritual theory.